Realizing Restorative Justice-Based Villages: Orientation and Formulation in a Progressive Legal Perspective - Ade Sathya Sanathana Ishwara (International Journal of Law, Crime and Justice, 2025)
The concept of restorative justice which emphasizes the recovery of victims as well as community participation is appropriate to be applied at the village level as an effort to create a village based on restorative justice. This study aims to formulate the idea of ​​a village based on restorative justice by involving community participation. This research is a normative legal research with a concept and statutory approach. The results of the study show that a village orientation based on restorative justice is intended to optimize the role of non-litigation dispute resolution in village communities. From a progressive legal perspective, a village based on restorative justice is a village with the aim of maintaining social harmony in resolving disputes in society. Therefore, the formation of Village Regulations is important as a guideline for implementing the concept of restorative justice in village communities.